2018
DOI: 10.1002/pc.25130
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic pressure control in VARTM: Rapid fabrication of laminates with high fiber volume fraction and improved dimensional uniformity

Abstract: The compaction pressure on the fibrous preform is one of the most critical parameters in vacuum assisted resin transfer molding (VARTM), which significantly affects the preform permeability, mold filling time, and final thickness of the fabricated composite. In this study, the compaction pressure on the vacuum bag was controlled during and after the mold filling to achieve rapid impregnation and improve the fiber volume fraction of the laminate. It was shown that the dynamic pressure control (1) enabled the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…The significant effect of applying external pressure on reducing the variation of the laminate thickness was also reported in Ref. [41].…”
Section: Resultssupporting
confidence: 57%
“…The significant effect of applying external pressure on reducing the variation of the laminate thickness was also reported in Ref. [41].…”
Section: Resultssupporting
confidence: 57%
“…The initial increase in fiber content, caused by the action of the compressive pressure, gradually stabilizes and then decreases below the value before the start of the infusion, which is caused by the increase in the internal pressure in the preform when it is filled with resin (see Figure 3d). This phenomenon is highly undesirable for the strength of the molded structure, which was thoroughly studied in [54], where an improvement of the process using additional external pressure is proposed. However, the modification of the presented modeling method in accordance with this improvement is a task for future research.…”
Section: Modeled Vacuum Infusion System Some Simulation Results and Predictive Criteriamentioning
confidence: 99%
“…A significant decrease in the fiber volume fraction, which is shown in Figure 17b, can also be eliminated only at the stage preceding the second stage of resin cure. Apparently, the best solution to this problem is the external controlled pressure technology proposed in [54]. Another important problem is related to the provision of the required thermal schedule during the implementation of the process by the out-autoclave method, when infrared irradiation of the preform can be effectively used [59].…”
Section: Discussionmentioning
confidence: 99%
“…37 In addition, it has been reported that the void size and location play significant roles in the transport of the voids and their mobility. 38,39 For instance, the mobility of the voids between the fiber tows is higher than the voids located within the tows. 40 Thus, the changes in void morphology such as size, shape, and location in different laminates were studied using scanning electron microscopy (SEM).…”
Section: Scanning Electron Microscopy Imagingmentioning
confidence: 99%